Neurotoxic and Teratogenic Effects of Enrofloxacin Against Newly Hatched Chicks Subjected to Omphalitis.: نبراس نائب عبد الحمزة وعروبة محمد سعيد ابراهيم - Abdulhamza, Nibras Naeb; Ibrahim, Orooba Mohammed Saeed (The Iraqi Journal of Veterinary Medicine, 2019)
This study was aimed to investigate any possible neurotoxic signs and teratogenic anomalies that may result from pre incubation dipping of fertile eggs in Enrofloxacin concentrations as a preventive measurement against omphalitis. E. Coli sensitivity against Enrofloxacin was examined in a dose dependent manner by using 2, 4, 6, 8, and 10 µg/ml. Forty two non-infected newly hatched chicks at age of 5-7 days were divided into six groups of seven chicks each, subjected to behavioral tests namely; Open Field Test and Tonic Immobility Test. For Open Field Test results showed that the lowest latency period was recorded significantly in chicks whose eggs dipped in 10µg/ml of Enrofloxacin (6±0.78 sec.) in comparison to control group (32.43±1.52 sec.) while the highest latency period was recorded insignificantly in chicks whose eggs dipped in 2µg/ of Enrofloxacin (29±1.61 sec.). The highest number of lines crossed by both feet was recorded significantly in chicks whose eggs dipped in 10µg/ml of Enrofloxacin (31.43 ±2.7) in comparison to control group (12.43 ±1.02) while the lowest number of lines crossed by both feet was recorded insignificantly in chicks whose eggs dipped in 2µg/ml of Enrofloxacin (14 ±1.87). The highest number of jumps was recorded significantly in chicks whose eggs dipped in 10µg/ml of Enrofloxacin (8.85 ±0.3) in comparison to control group (1.14 ±1.0) while the lowest number of jumps was recorded insignificantly in chicks whose eggs dipped in 2µg/ml of Enrofloxacin (2 ±0.17). The highest number of defecation times was recorded significantly in chicks whose eggs dipped in 10µg/ml of Enrofloxacin (1.6 ±0.23) in comparison to control group (0.86 ±0.26) while the number of defecation times were insignificant in the rest of groups. Both of call and backing times in all groups were insignificant in comparing with control group. Results for Tonic Immobility Test showed that shortest time needed by the chick to upright itself and stand unaided was recorded significantly in chicks whose eggs dipped in 10µg/ml of Enrofloxacin (1 sec. ±0.1) in comparing with control group (2 sec. ±0.11) while the longest time needed by the chick to upright itself and stand unaided was recorded insignificantly in chicks whose eggs dipped in 2µg/ml of Enrofloxacin (1.8 sec. ±0.1). Pre-incubation dipping of fertile eggs in Enrofloxacin concentrations showed insignificant changes in body weight, body length, leg length, wing length and beaker length. We concluded that using low concentrations of of Enrofloxacin and Ciprofloxacin to dip eggs in has resulted in minimized neurotoxic and teratotgenic effects.